Everyday Life Cognitive Instability Predicts Simple Reaction Time Variability: Analysis of Reaction Time Distributions and Delta Plots. Issue 1 (20th October 2015) - Steinborn, Michael B.; Langner, Robert; Flehmig, Hagen C.; Huestegge, Lynn
Summary: The goal of this study is to understand the interface between subjectively assessed and objectively measured attention functioning. To this end, we assessed both self‐report data using the Cognitive Failures Questionnaire (CFQ) and sustained‐attention performance using a low‐demand psychomotor vigilance task that required participants to respond to visual targets. Unlike previous studies, reliability of task performance was ensured, testing individuals twice within a retest interval of 1 week. Given that everyday life attentional lapse tendencies vary even in normal‐population samples, we asked whether there is a relationship with laboratory performance, in general and as a consequence of time on task (TOT). As a result, low (versus high) CFQ scorers were somewhat different in their average response speed but became particularly prone to lapsing during the task period, as reflected in standard measures of response‐speed variability as well as ex‐Gaussian parameters of distributional skewness. In conclusion, we argue that persistence to sustained demand might be an important aspect of construct validity that must be evoked by a manipulation of TOT, which may be useful for the evaluation of questionnaires in ecologically valid situations. Copyright © 2015 John Wiley & Sons, Ltd.